Continuous response to maintenance fuzuloparib for germline BRCA2- mutated metastatic pancreatic adenocarcinoma: a case report and literature review - Zhang, Chenyan; Zhang, Pei; Cheng, Ke; Cao, Dan (Frontiers in Pharmacology, 2025)
Pancreatic adenocarcinoma with germline BRCA mutations (gBRCAm) represents a distinct molecular subtype with enhanced sensitivity to platinum-based chemotherapy and poly (ADP-ribose) polymerase inhibitors (PARP inhibitors). Fuzuloparib is a novel, potent, and orally bioavailable PARP inhibitor. Despite showing improved efficacy and a more favorable safety profile compared to olaparib in preclinical studies, clinical evidence for its application in pancreatic adenocarcinoma harboring gBRCAm remains limited. We report here a 33-year-old Asian woman with extensively metastatic pancreatic adenocarcinoma harboring a germline BRCA2 nonsense mutation who a durable response to fuzuloparib after NALIRIFOX chemotherapy. Her progression-free survival exceeded 15 months with ongoing fuzuloparib maintenance therapy for over 7 months. This case underscores the important role of biomarker-directed therapy in pancreatic adenocarcinoma and fuzuloparib may represent a potential PARP inhibitor option for maintenance treatment in pancreatic adenocarcinoma with gBRCAm. However, large-scale randomized controlled trials are needed to validate these results.